2011
DOI: 10.1063/1.3528119
|View full text |Cite
|
Sign up to set email alerts
|

Observation of negative capacitances in Al/P(VDF-TrFE)/SiO2/nSi structures

Abstract: Metal-insulator-semiconductor structures with thin films of the ferroelectric copolymer poly(vinylidene fluoride trifluoroethylene) on oxidized n-silicon exhibit negative capacitances, i.e., inductivelike behavior. The magnitude of negative capacitances depends besides on the layer properties also on frequency and bias. Additional time domain measurements confirm the inductive character. A qualitative model for this behavior based on space charge limited currents is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It was observed that the capacitance of the r-ELDs becomes negative for sufficiently high applied biases and low modulation frequencies. This negative capacitance (NC) behaviour has been reported previously for different type of devices like solar cells [2,3], p-i-n diodes [4], Schottky diodes [5,6] metal-insulator-semiconductor structures [7] including electroluminescent diodes [1,[8][9][10][11]. However, the explanations given by various groups for the occurrences of NC do not agree to a common argument.…”
Section: Introductionmentioning
confidence: 65%
“…It was observed that the capacitance of the r-ELDs becomes negative for sufficiently high applied biases and low modulation frequencies. This negative capacitance (NC) behaviour has been reported previously for different type of devices like solar cells [2,3], p-i-n diodes [4], Schottky diodes [5,6] metal-insulator-semiconductor structures [7] including electroluminescent diodes [1,[8][9][10][11]. However, the explanations given by various groups for the occurrences of NC do not agree to a common argument.…”
Section: Introductionmentioning
confidence: 65%
“…If the imaginary part is positive the effective terminal behavior is capacitive and if it is negative the effective terminal effect is inductive. [6][7][8][9][10][11] In recent years, some researchers have reported a negative capacitance (NC) [6][7][8][9][10][11][12][13] or negative dielectric constant (NDC) [14][15][16] in the forward bias C-V characteristics in some devices. The observation of NDC and NC are important because they imply that an increment of bias voltage produces a decrease in the charge on the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Salahuddin suggested that the ferroelectric transistor could provide a new mechanism to amplify the surface potential above the gate voltage due to the negative capacitance effect [1,2]. Several experiments showed proof of negative capacitance in ferroelectric materials [3,4]. Recent studies propose a non-hysteretic behavior of negative capacitance FET with a subthreshold slope less than 30 mV/dec, but the device is only in the simulation state [5].…”
Section: Introductionmentioning
confidence: 99%